PHYTOCHEMICAL ANALYSIS AND in vitro ANTIOXIDANT AND ANTIBACTERIAL ACTIVITIES OF ETHANOLIC LEAF EXTRACT OF Achyranthes aspera L. (Applied Biological Research, 2023)
The present study was aimed to evaluate the phytochemicals present in the  ethanolic extract of Achyranthes aspera leaves (EEAA) and identify the bioactive compounds by GC-MS analysis. In vitro antioxidant activity was  measured by using DPPH, metal chelating and superoxide radical scavenging assays. The anti-bacterial activity was assayed by disc diffusion  method. The results revealed the presence of phenols, flavonoids, and  tannins in significant amount in EEAA [372 ± 2 mg GAE g-1, 22.6 ± 1.34 mg  CE g-1 and 242 ± 2 mg TAE g-1, respectively. GC-MS analysis revealed the  presence of 20 major bioactive compounds with 74.36% total leaf extract, dominated by phytol (10.67%), palmitic acid (6.56%), pseudo-ephedrine (6.06%) and hexacosane (5.76%). EEAA exhibited a maximum DPPH  radical scavenging activity of 46.3%. The metal chelation activity in EEAA was 58.8%. The EEAA exhibited a maximum of 46.51% superoxide scavenging activity. In vitro antibacterial activity of EEAA assayed against  three human pathogenic bacteria viz., Salmonella typhi, Bacillus subtilisand Escherichia coli. EEAA showed maximum inhibition against B. subtilis (16.33 ± 0.577 mm). The study revealed that A. aspera is a potential  source for developing health-oriented products.
Keywords: Achyranthes aspera; antibacterial; antioxidants; flavonoid; GC-MS analysis; leaf extract; phenols; phytoconstituents